2017
DOI: 10.30971/pje.v32i1.52
|View full text |Cite
|
Sign up to set email alerts
|

Prospective Teachers’ Perception of Engagement in Active Learning Through Peer Teaching and Peer Assessment

Abstract: The study intends to investigate the perceptions of higher education students about their engagement in active learning through peer-teaching and peer-assessment. A group of 22 students comprising nine female and thirteen males participated in the study. The researchers taught the course within six weeks, and then divided it amongst students through assignments. The students prepared it, discussed with researchers, shared and taught the assigned part of the course to their peers in the classroom in the presenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 56 publications
1
3
0
Order By: Relevance
“…The findings of previous research on the impact of teachers' training were mixed, with some supporting this study and others not. However, the results of the NAHE (Phase-I) project demonstrated that faculty development courses had significantly advanced the teaching abilities of university teachers across Pakistan (Sarwar et al, 2017). The findings of a study conducted in Korea back in 2005, which evaluated the effectiveness of coaching on the leadership competency of teachers, are consistent with the results of the current study.…”
Section: Discussionsupporting
confidence: 86%
“…The findings of previous research on the impact of teachers' training were mixed, with some supporting this study and others not. However, the results of the NAHE (Phase-I) project demonstrated that faculty development courses had significantly advanced the teaching abilities of university teachers across Pakistan (Sarwar et al, 2017). The findings of a study conducted in Korea back in 2005, which evaluated the effectiveness of coaching on the leadership competency of teachers, are consistent with the results of the current study.…”
Section: Discussionsupporting
confidence: 86%
“…To put it another way, teachers' professional and individual features have a role to play in enhancing professional development effectiveness. This view is supported by Sarwar et al, [40] and Kennedy [42] who suggest that effective professional development should focus on specific problems faced by teachers rather than pedagogic theory. In essence, these authors advocates a problem-solving approach related to teachers' needs for actual classroom practice.…”
Section: Research On Formal Professional Development Effectivenessmentioning
confidence: 96%
“…The importance of experienced and efficient professional development organizers and facilitators to professional development success is also proved by Sarwar et al when these authors compare the effectiveness of two professional development phases (pp. 17) [40]. Meanwhile, Menges shows that the interplay between the personal context (i.e., teacher personality -individual feature) and an element of the professional development activity (i.e., mentors -professional development providers) contributes to professional development success [41].…”
Section: Research On Formal Professional Development Effectivenessmentioning
confidence: 99%
See 1 more Smart Citation